Purification, partial structural characterization and health benefits of exopolysaccharides from potential probiotic Pediococcus acidilactici NCDC 252. (December 2020) - Kumar, Raman; Bansal, Poonam; Singh, Jasbir; Dhanda, Suman
Graphical abstract: Highlights: Gene cluster for exopolysaccharides biosynthesis was identified for the first time in genome of any species of Pediococcus acidilactici (NCDC 252). Exoplysaccharides were purified and found to be α-glucan having CO, C–H and OH groups.. Exopolysaccharides exhibited antioxidant-reduction potential in dose dependent manner. Anti-cancer activity of exopolysaccharides was observed in HCT116 cell line. Abstract: Probioceuticals are probiotic-derived biologically active compounds that positively influence human health. Exopolysaccharides (EPS) are long chain polymers of sugars and their derivatives with diverse biological functions. The objective of this work was to study EPS from Pediococcus acidilactici (PA) NCDC 252, a potential probiotic. In silico analysis of PA NCDC 252 genome revealed an EPS gene cluster (10 genes) and genes were further analysed for their functional domains and products. EPS from PA NCDC 252 were purified by ethanol precipitation and gel filtration chromatography on Sephadex G-100. Molecular mass of purified EPS was 89.1 KDa as determined by gel filtration chromatography. Structural and component analysis by FTIR, NMR and UPLC revealed purified EPS to be linear homopolysaccharides (α-glucans) with few α-(1→3) branches. in vitro studies showed anti-oxidant, reduction potential and anti-cancer activity in dose dependent manner. Total antioxidant potential of EPS was 11.9 %. In-vitro cell viability assay revealed anti-proliferative effect of EPS on human colon cancer cell line (HCT116). At 10 and 100 μg/mL, EPS inhibited HCT116 cells up to 67.1 % and 87.3 % respectively. These results suggest that PA EPS can be therapeutically used as anti-oxidant and anticancer agent after in vivo studies.